Effectiveness of chlorhexidine gel and calcium hydroxide paste with chlorhexidine as intracanal medicaments in Enterococcus faecalis elimination - Martínez Guzhñay, Andrea Carolina (2021)
The aim of this study was to know the effectiveness of chlorhexidine gel and calcium hydroxide paste with chlorhexidine as intracanal medicaments in Enterococcus faecalis (E. faecalis) elimination. A bibliographic review was done through an exhaustive search in different databases such as: PubMed, ScienceDirect, Scielo, Springer, Google Scholar. Using inclusion and exclusion criteria, 37 articles published in the period 2003-2020 were selected, which were especially focused on E. faecalis and intracanal medication. The analysis showed that chlorhexidine in a higher percentage was the most effective intracanal medication in an average time of 7 days, followed by the combination of calcium hydroxide plus chlorhexidine that acted in the same way eliminating E. faecalis from the root canals, while calcium hydroxide did not show any antimicrobial activity against E. faecalis.